Análisis y medición del estrés térmico y la implementación de un protocolo de apoyo para el laboratorio de seguridad industrial de la Universidad Técnica de Cotopaxi - Molina Cajas, José Esteban (2016)
Speaking of heat stress undoubtedly reminds us of the conditions of heat or cold to which workers are exposed. The main objective of this investigation was focused on the need to propose a protocol to support the Laboratory of Industrial Security at Universidad Técnica de Cotopaxi. This protocol contributed to establish the methodological and standardized steps that should be applied at the time of measuring the thermal conditions for labor performance. During the investigation, a study was performed to the plant of the Corporación Ecuatoriana de Aluminio CEDAL S.A., same that has several production processes in which workers are exposed to machines that generate high temperatures and can cause damage to their physical and mental integrity….